2009
DOI: 10.1097/jto.0b013e3181b9ecca
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative versus Postoperative Chemotherapy in Patients with Resectable Non-small Cell Lung Cancer: Systematic Review and Indirect Comparison Meta-Analysis of Randomized Trials

Abstract: In patients with resectable lung cancer, there was no evidence of a difference in overall and disease-free survival between the timing of administration of chemotherapy (postoperative versus preoperative).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(95 citation statements)
references
References 59 publications
3
89
0
3
Order By: Relevance
“…Despite having been studied separately in the past, accumulating evidence suggests that tumour metastasis and chemoresistance not only commonly present simultaneously clinically but might also be intrinsically associated biological events45. It was observed, for example, that NSCLC patients with stage IV disease exhibit a substantially lower overall response rate to chemotherapy than patients with locally advanced disease67, suggesting that metastatic NSCLC patients are prone to be more resistant to chemotherapy in the clinic. In parallel, several biological events causing concurrent tumour metastasis and chemoresistance have been reported89.…”
mentioning
confidence: 99%
“…Despite having been studied separately in the past, accumulating evidence suggests that tumour metastasis and chemoresistance not only commonly present simultaneously clinically but might also be intrinsically associated biological events45. It was observed, for example, that NSCLC patients with stage IV disease exhibit a substantially lower overall response rate to chemotherapy than patients with locally advanced disease67, suggesting that metastatic NSCLC patients are prone to be more resistant to chemotherapy in the clinic. In parallel, several biological events causing concurrent tumour metastasis and chemoresistance have been reported89.…”
mentioning
confidence: 99%
“…Although this difference makes a formal indirect comparison of the effects of preoperative and postoperative chemotherapy difficult, the benefit noted is on a similar scale. Others have attempted formal comparison based on aggregate data 8 and concluded the effect of chemotherapy on overall or recurrence-free survival is similar, irrespective of chemotherapy timing. However, they did not include key large trials, published more recently, and have included a trial confounded by the use of radiotherapy in only one arm 40 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, an indirect methodology meta-analysis had shown that NCT was similar to adjuvant chemotherapy in terms of survival benefit provided [32]. These findings taken together suggest that when chemotherapy is indicated in stage 2 or 3 disease, NCT or adjuvant chemotherapy are reasonable options in suitable patients.…”
Section: Discussionmentioning
confidence: 99%